Alibaba’s innovation-driven approach to intellectual property rights governance - CHEN, Liang (Institutional Knowledge at Singapore Management University, 2024)
Set in March 2024, one year after Alibaba Group announced its largest-ever restructuring in history, this case traces the behemoth’s journey in protecting Intellectual Property (IP) on its e-commerce platforms, primarily Taobao and Tmall, China’s largest online shopping platforms. Alibaba formally implemented its IP protection mechanism in 2002. By the mid-2010s, the company had established a comprehensive IP protection regime based on three innovative pillars: technology empowerment, institutional innovation, and multi-party co-governance. Through technology empowerment, Alibaba leveraged advanced digital technologies such as artificial intelligence (AI), data mining, blockchain, and cloud computing to automate the detection of counterfeit products and remove their listings from its platforms. Institutional innovation involved creating platform-based solutions that offered IP protection beyond the frameworks established by formal legal and regulatory institutions – such as the Protection of Original Designs initiative designed to support small business owners and innovators. The multi-party co-governance approach brought together key stakeholders including government agencies, rights holders, and consumers, through long-term partnerships like the Alibaba Anti-Counterfeiting Alliance. Over the past two decades, Alibaba had made significant strides in anti-counterfeiting efforts. However, the e-commerce giant continued to face the dual challenge of reducing the prevalence of counterfeiting while increasing the diversity of brands and sellers in its e-marketplaces. Amidst the evolving landscape of domestic regulations, continual pressure from trade agencies abroad, and increasingly sophisticated counterfeiters, how could Alibaba navigate the competing demands of promising safeguards of IP rights while maintaining growth momentum? Students will learn about IP concepts and the differences in the IP-related issues between brick-and-mortar and e-commerce contexts. They will explain the significance of IP governance by e-commerce platforms, identify the main challenges e-commerce platforms face, and examine the key strategies to address them. They will also discuss the competing demands that these platforms must balance, that is, combating counterfeiting while pursuing growth.